Pengaruh Aset Pajak Tangguhan, Nilai Perusahaan dan Perencanaan Pajak terhadap Manajemen Laba - Permata, Yangki; Kusuma Dewi, Eka (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2024)
Earnings management is an effort made by management to attract investors or stakeholders by influencing its financial reports. Earnings management is one way of processing accounting data through deferred tax assets and tax planning so as to increase public confidence in the company's performance. This study aims to determine the influence of deferred tax assets, company value and tax planning on earnings management in Consumer Non-Cyclical companies listed on the Indonesia Stock Exchange for the 2018-2022 period. The sampling method in this study used a purposive sampling method, in order to obtain a data sample of 9 companies or 45 observational data. Source of data used in this research is secondary data. Data analysis wasperformed by panel data regression analysis using Eviews 12. The results of the study Partially deferred tax assets and tax planning has no effect on earning management. While company value have an effect on earnings management. Simultaneously deferred tax assets, company value and tax planning have an effect on earnings management.